Identifikasi Rendahnya Hasil Belajar Peserta Didik saat Pembelajaran Daring Menggunakan Aplikasi WhatsApp Mata Pelajaran IPA Kelas V SDN 7 Menteng - Diana Putri; Nurul Hikmah Kartini; Dedy Setyawan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This research was carried out aimed at describing the factors causing the low learning outcomes of students during online learning using the application WhatsApp on science subjects. The method used in this research is a qualitative method with a type of case study. The data collection techniques used were observation, interviews, and documentation. The object studied was 3 students, class teachers, and triangulation of data on school principals, school operators (TU), and students' parents. The results of the research conclusions indicated that: (1) students were less interested in participating in online learning in science subjects. (2) Students do not like science subjects online. (3) the teacher only uses the WhatsApp application to carry out online learning. (4) the teacher only notifies and sends the material to be studied without being explained first. (5) the teacher always gives assignments to students so that it makes students dislike online learning. (6) the students are less motivated to take part in learning.